Monitoring compliance with high-level commitments in health: the case of the CARICOM Summit on Chronic Non-Communicable Diseases - T Alafia Samuels; John Kirton; Jenilee Guebert (The World Health Organization, 2014)
The CARICOM Summit on Chronic Non-Communicable Diseases - the first government summit ever devoted to noncommunicable diseases (NCDs) - was convened by the Caribbean Community (CARICOM) in Trinidad and Tobago in September 2007. Leaders in attendance issued the declaration of Port of Spain, a call for the prevention and control of four major NCDs and their risk factors. An accountability instrument for monitoring compliance with summit commitments was developed for CARICOM by the University of the West Indies in 2008 and revised in 2010. The instrument - a one-page colour-coded grid with 26 progress indicators - is updated annually by focal points in Caribbean health ministries, verified by each country's chief medical officer and presented to the annual Caucus of Caribbean Community Ministers of Health. In this study, the G8 Research Group's methods for assessing compliance were applied to the 2009 reporting grid to assess each country's performance. Given the success of the CARICOM Summit, a United Nations high-level meeting of the General Assembly on the prevention and control of NCDs was held in September 2011. In May 2013 the World Health Assembly adopted nine global targets and 25 indicators to measure progress in NCD control. This study shows that the CARICOM monitoring grid can be used to document progress on such indicators quickly and comprehensibly. An annual reporting mechanism is essential to encourage steady progress and highlight areas needing correction. This paper underscores the importance of accountability mechanisms for encouraging and monitoring compliance with the collective political commitments acquired at the highest level.